1984
DOI: 10.1111/j.1476-5381.1984.tb10777.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐potassium ATPase inhibition potentiates compound 48/80‐induced histamine secretion from mast cells

Abstract: 1The effect of ouabain on the histamine secretion induced by compound 48/80 has been studied using rat peritoneal mast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
2

Year Published

1985
1985
1993
1993

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
4
10
2
Order By: Relevance
“…Pearce (1982) suggested that calcium reservoirs deep within the cell membrane were the most likely location of the intracellular calcium stores involved in histamine secretion elicited in calcium-free media. We recently observed that the inhibition of mast cell sodium-potassium ATPase, in the presence of low calcium concentrations, potentiated the immunological histamine release ) and the release induced by compound 48/80 (Amellal et al, 1984;Binck et al, 1985). These potentiations were inhibited by EGTA and lanthanum, observations that are in agreement with the involvement of an increase of putative membranous calcium stores.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…Pearce (1982) suggested that calcium reservoirs deep within the cell membrane were the most likely location of the intracellular calcium stores involved in histamine secretion elicited in calcium-free media. We recently observed that the inhibition of mast cell sodium-potassium ATPase, in the presence of low calcium concentrations, potentiated the immunological histamine release ) and the release induced by compound 48/80 (Amellal et al, 1984;Binck et al, 1985). These potentiations were inhibited by EGTA and lanthanum, observations that are in agreement with the involvement of an increase of putative membranous calcium stores.…”
Section: Introductionsupporting
confidence: 71%
“…These potentiations were inhibited by EGTA and lanthanum, observations that are in agreement with the involvement of an increase of putative membranous calcium stores. However, the possibility that some minute influx of calcium, sufficient to induce exocytosis, might occur from the extracellular medium was not excluded (Amellal et al, 1984). Our concern in the present paper was to check this hypothesis using ionophore A23187 as a triggering agent of mast cell secretion, considered to bypass the plasma membranedependent steps of the regulation of exocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…The secretory responses of mast cells and other tissues are enhanced by digitalis glycosides (Vizi, 1978;Frossard et al, 1983;Powis, 1983;Amellal et al, 1984;1985 and references therein;Binck et al, 1985). Recently, we characterized the Na+-K+ pump mechanism in intact peritoneal mast cells of the rat and provided evidence for modulation of the pump activity by changes in the sodium permeability of the plasma membrane by extracellular calcium (Knudsen & Johansen, 1989a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The Na+/K'-pump in the plasma membrane of mast cells [5] is inhibited by ouabain, and this allows the accumulation of sodium inside the cells. The enhancement by ouabain of histamine release develops gradually over 0.4-l h [2,3], and it is likely to be related to the accumulation of sodium, which may induce changes in a pool of calcium bound to the plasma membrane [4]. Erjavec and Ferjan [6] reported that hydrophilic digitalis glycosides enhance histamine release from rat mast cells induced by compound 48/80, while more lipophilic glycosides inhibit histamine release.…”
Section: Introductionmentioning
confidence: 99%